Postcolonial Discourse in Coogler’s Black Panther: A Multimodal Critical Discourse Analysis - Albert Tallapessy; Indah Wahyuningsih; Riska Ayu Anjasari (Humaniora, 2020)
This article deals with the investigation of the existence of postcolonial discourse in Coogler’s Black Panther (2018). The study aims to reveal and examine the existence of social issues related to Bhabha’s notion of postcolonialism represented through visual and linguistic elements in the movie. Fairclough’s (1989,2001, 2010) Critical Discourse Analysis, Kress and van Leeuwen’s (2006) Reading Images, Halliday’s Systemic Functional Linguistics (2004) and Bhabha’s (1994) Postcolonialism are used to conduct this research. The result of the study shows that postcolonial discourse is proved represented in the movie. The findings imply that the post colonialism affects the characters in term of how they see and reflect themselves towards the dominance. They are also identified as possessing hybrid identity, ambivalence, and mimicry. It seems that the result of the research opposes the director’s intention to bring the theme of the movie. Theoretically, it is proved that the social irregularities representing black supremacy and exploitation of the citizen of Africa, Wakanda, is depicted in the movie. Empirically, the existence of nondemocratic social practices in black citizens is also seen in the movie.